A Safe Harbor in the Opioid Crisis: How The Federal Government Should Allow States to Legislate for Safe Injection Facilities in Light of the Opioid Public Health Emergency - Leary, Amber A. (2019)
Opioid addiction is wreaking havoc across the United States, leading to a shocking number of overdoses and deaths. This epidemic has prompted the Trump Administration to declare opioid abuse a public health emergency and to call for increases in evidence-based treatment for those addicted to harmful opioids. To combat this epidemic, some cities have embraced one such evidence-based treatment plan—safe injection facilities—which are infirmaries where drug users can inject pre-obtained drugs under the supervision of nurses or overdose reversal specialists who can respond in real time to prevent overdose and death. Though safe injection facilities outside the United States have been proven effective in reducing overdose deaths and in helping addicts seek treatment, the United States Department of Justice, however, has been unequivocal in its position on safe injection facilities: they are illegal under the federal Controlled Substances Act. This note argues that the federal government should allow states to implement new strategies for tackling the opioid crisis. Additionally, this note proposes that the either the legislative or the executive branch of the federal government should allow states to establish safe injection facilities through an amendment to the Controlled Substances Act, deeming safe injection facilities healthcare institutions, or by establishing a DOJ policy not to prosecute owners and clients of safe injection facilities. These approaches would allow states to test the effectiveness of safe injection facilities in different areas of the country, while also destigmatizing abuse, which can lead to increased treatment for drug users